Menakar Nilai, Mengelola Resiko : Peran dan Tantangan Penaksir dalam Industri Gadai - Sri Astuti Nasir; Indri Iswardhani; A. Reski Almaida dg Macenning; Nulthazam Sarah; Nur Fadilah Ayu Sandira (Jurnal Online Manajemen ELPEI, 2025)
This study aims to analyze the role of appraisers in determining the pawn value, the objectives of the appraisal process, vigilance in asset valuation, and the challenges faced by appraisers in performing their duties. This research employs a qualitative method with a descriptive approach through a literature study. The data sources used are secondary data, including asset appraisal theories, previous studies, and applicable regulations in the pawn industry. The data analysis technique is conducted descriptively to systematically and accurately describe the existing conditions. The findings indicate that asset appraisal in the pawn industry faces various challenges, such as market price fluctuations, the risk of manipulation, and economic uncertainty. Therefore, it is necessary to enhance appraisers' competencies, implement stricter supervision systems, and utilize technology in the valuation process to improve transparency and work efficiency. By understanding the roles and challenges faced, the pawn industry can develop better strategies to manage risks and improve appraisal accuracy. Keywords: Pawn appraisal, appraiser’s role, collateral value, appraisal risk, pawn industry regulations.